COMPARISON OF REGIONAL BUDGET TRANSPARENCY BETWEEN PEKANBARU CITY AND BENGKALIS REGENCY - Nurmasari; Harapan Tua (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to explore and analyze the comparative level of regional budget transparency between Pekanbaru City and Bengkalis Regency based on the availability of budget documents, financial reports, and public information accessibility through official local government websites. The data used are official documents published by the Regional Financial and Development Supervisory Agency (BPKAD), the Regional Public Information Agency (PPID), the Central Statistics Agency (BPS), and local government websites. The literature review indicates that both regions have implemented transparency principles, but Bengkalis has more comprehensive documents available on the PPID portal, while Pekanbaru demonstrates consistent publication of its Regional Government Accountability Report (LKPD) and annual budget documents. This research provides input for local governments to improve the quality of fiscal information disclosure.